Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.3390/ma16237496
|View full text |Cite
|
Sign up to set email alerts
|

Pervious Concrete Made with Recycled Coarse Aggregate and Reinforced with Date Palm Leaves Fibers

Adil Tamimi,
Sami W. Tabsh,
Magdi El-Emam

Abstract: This study considers 12 pervious concrete mixes incorporating 100% recycled coarse aggregate from old concrete demolition waste and containing various amounts of natural fine aggregate and date palm leaves fibers. First, the properties of the recycled aggregate in terms of their particle size distribution, abrasion resistance, crushing values, specific gravity and water absorption are obtained. Next, the pervious concrete density, compressive strength, tensile strength, permeability and porosity are determined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…Lima et al [20] reported that incorporating Hydroxypropyl methylcellulose (HPMC) with 50% RCA, alongside a superplasticizer, improved the mechanical properties of RAPC without compromising its permeability. Further, Tamimi et al [21] found that the addition of date leaf fibers slightly affected the compressive strength of RAPC, yet significantly enhanced its tensile strength. Aliabdo et al [22] examined the effects of various fibers and styrene-butadiene latex on the properties of RAPC, noting that polypropylene fibers and styrene-butadiene latex positively influenced the strength index, whereas rubber fibers reduced both compressive and tensile strengths.…”
Section: Introductionmentioning
confidence: 99%
“…Lima et al [20] reported that incorporating Hydroxypropyl methylcellulose (HPMC) with 50% RCA, alongside a superplasticizer, improved the mechanical properties of RAPC without compromising its permeability. Further, Tamimi et al [21] found that the addition of date leaf fibers slightly affected the compressive strength of RAPC, yet significantly enhanced its tensile strength. Aliabdo et al [22] examined the effects of various fibers and styrene-butadiene latex on the properties of RAPC, noting that polypropylene fibers and styrene-butadiene latex positively influenced the strength index, whereas rubber fibers reduced both compressive and tensile strengths.…”
Section: Introductionmentioning
confidence: 99%
“…The incorporation of low-cost materials into pervious concrete for improving mechanical performance is also extended to natural or synthetic fibers, such as high-strength glass fibers [17,18], carbon fibers, cured carbon composite fibers, date palm leaf fibers [19], palm oil kernel shell fibers [20], cellulose fibers, natural kenaf fibers, steel fibers [18], coppercoated fibers, amorphous metallic fibers, hemp fibers, seashell fibers [20], polypropylene fibers [9], polyolefin fibers, polyester fibers, polyethylene fibers, ferro-green, green-net fibers, polyvinyl alcohol fibers, polyvinyl chloride fibers, recycled rubber fibers, waste plastic fibers, Kevlar fibers, polyacrylonitrile fibers, waste cloth strip barchip fibers, basalt fibers, etc. [21] Steel and polypropylene fiber inclusion increases abrasion and permeability performance, respectively [9].…”
Section: Introductionmentioning
confidence: 99%
“…Using some solid waste to produce pervious concrete can effectively treat solid waste while reducing the use of construction materials and carbon emissions [21]. Many scholars have conducted research including using solid waste, such as recycled coarse aggregate [22][23][24], coal bottom ash aggregates [25], rice husk ash [26], waste glass [27], metakaolin [28], and fly ash [29], to produce pervious concrete.…”
Section: Introductionmentioning
confidence: 99%